Sử dụng phân tích hướng đối tượng để phát triển những hệ thống lớn tích hợp - Ban, Đoàn Văn (Journal of Computer Science and Cybernetics, 2016)
This paper will discuss an oject-oriented analysis used in the development of integrated information systems. A system can be viewed as a collection of entities that interact together to accomplish certain objectives. In oject-oriented analysis, the entities are called the objects. Oject-oriented analysis refers to the methods of specifying of the software in terms of real-world objects, their behavior, and their interactions. Oject-oriented desig on the other hand, turns the software requirements into specifications for objects and derives class hierarchies from which the objects can be created. The steps of oject-oriented system development are described here. After that, we present a prototype simulating telecommunication services based on the use of oject-oriented techniques. The general object model designed to process the telecommunication services is introduced and explained.